Lauric Acid Production in a Glycogen-Less Strain of Synechococcus sp. PCC 7002 - Work, Victoria H.; Melnicki, Matthew R.; Hill, Eric A.; Davies, Fiona K.; Kucek, Leo A.; Beliaev, Alexander S.; Posewitz, Matthew C. (Frontiers in Bioengineering and Biotechnology, 2015)
The cyanobacterium Synechococcus sp. PCC 7002 was genetically engineered to synthesize biofuel compatible medium-chain fatty acids during photoautotrophic growth. Expression of a heterologous lauroyl-acyl carrier protein (C12:0-ACP) thioesterase with concurrent deletion of the endogenous putative acyl-ACP synthetase led to secretion of transesterifiable C12:0 fatty acid in CO2-supplemented batch cultures. When grown at steady state over a range of light intensities in an LED turbidostat photobioreactor, the C12-secreting mutant exhibited a modest reduction in growth rate and increased O2 evolution relative to the wildtype. Inhibition of i) glycogen synthesis by deletion of the glgC-encoded ADP-glucose pyrophosphorylase (AGPase), and ii) protein synthesis by nitrogen deprivation were investigated as potential mechanisms for metabolite redistribution to increase fatty acid synthesis. Deletion of AGPase led to a ten-fold decrease in reducing carbohydrates and secretion of organic acids during nitrogen deprivation consistent with an energy spilling phenotype. When the carbohydrate-deficient background (∆glgC) was modified for C12 secretion, no increase in C12 was achieved during nutrient replete growth, and no C12 was recovered from any strain upon nitrogen deprivation under the conditions used. At steady state, the growth rate of the ∆glgC strain saturated at a lower light intensity than the wildtype, but O2 evolution was not compromised and became increasingly decoupled from growth rate with rising irradiance. Photophysiological properties of the ∆glgC strain suggest energy dissipation from photosystem II and reconfiguration of electron flow at the level of the plastoquinone pool.